The development of a problem-based learning design model to improve students' communication skills - Nanang Saputro; Een Yayah Haenilah; Muhammad Mona Adha (International Journal of Educational Studies in Social Sciences (IJESSS), 2022)
The purpose of this study was to develop a problem-based learning model for fourth-grade elementary school students in order to improve their communication skills. This is a research and development (R&D) project using a combined approach (mixed methods), specifically Borg and Gall research combined with ADDIE design development. The type of research that was conducted was True Experimental research with a post-test only control group design. Data collection techniques included tests and non-tests. The effectiveness of the problem-based learning model was determined through data analysis using the t-test. The results indicated that t arithmetic > t table (9.84 > 2.012) was rejected at a 5% significance level, while Ha was accepted and supported by observations of student communication skills in six lessons, which revealed an average of 80.07 percent of 24 students in the very good category. As a result, it can be concluded that the design model for problem-based learning is effective at improving communication skills.